Natural Nanoparticles: A Particular Matter Inspired by Nature - Sharoon Griffin; Muhammad Irfan Masood; Muhammad Jawad Nasim; Muhammad Sarfraz; Azubuike Peter Ebokaiwe; Karl-Herbert Schäfer; Cornelia M. Keck; Claus Jacob (MDPI AG, 2017)
During the last couple of decades, the rapidly advancing field of nanotechnology has produced a wide palette of nanomaterials, most of which are considered as "synthetic" and, among the wider public, are often met with a certain suspicion. Despite the technological sophistication behind many of these materials, "nano" does not always equate with "artificial". Indeed, nature itself is an excellent nanotechnologist. It provides us with a range of fine particles, from inorganic ash, soot, sulfur and mineral particles found in the air or in wells, to sulfur and selenium nanoparticles produced by many bacteria and yeasts. These nanomaterials are entirely natural, and, not surprisingly, there is a growing interest in the development of natural nanoproducts, for instance in the emerging fields of phyto- and phyco-nanotechnology. This review will highlight some of the most recent-and sometimes unexpected-advances in this exciting and diverse field of research and development. Naturally occurring nanomaterials, artificially produced nanomaterials of natural products as well as naturally occurring or produced nanomaterials of natural products all show their own, particular chemical and physical properties, biological activities and promise for applications, especially in the fields of medicine, nutrition, cosmetics and agriculture. In the future, such natural nanoparticles will not only stimulate research and add a greener outlook to a traditionally high-tech field, they will also provide solutions-pardon-suspensions for a range of problems. Here, we may anticipate specific biogenic factories, valuable new materials based on waste, the effective removal of contaminants as part of nano-bioremediation, and the conversion of poorly soluble substances and materials to biologically available forms for practical uses.